STRATEGI PENGELOLAAN DAN PENGEMBANGAN MUSEUM ARMA SEBAGAI SEBUAH LIVING MUSEUM - Setiyarti, Tettie; Sundari, Pipit; Anggarwati Dewi, Kadek Ratih (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
The Living Museum is not only based on the participation of the community where it is located, but can also act as a vehicle that directly introduces the sociocultural development and growth in the area. This paper, using SWOT analysis, will try to examine the management strategy and development implemented by the Arma Museum as a Living Museum, which is located in Ubud, Bali. The qualitative study on which this paper is based was focused on examining the management strategy and development applied by the Arma Museum. As a result, the study found that various programs and activities held by the Arma Museum are not merely to showcase the beauty of Balinese art and culture, but are also intended as a vehicle for conservation as well as for the future development of Balinese arts in general. So, the management strategy of the Arma Museum as a Living Museum can be implemented with various strategic programs, such as: tourism product development strategies, strengthening the potential that is the hallmark of the Arma Museum, and promoting the existence of the Arma Museum